Analysis of Therapeutic Communication of Delima Midwives in Antenatal Care Services in Pekanbaru City - Kiki Megasari; Widya Juliarti (Journal of Midwifery and Nursing, 2021)
The number of MMR in Indonesia is high among ASEAN countries, one of the causes is the low level of health services obtained during pregnancy. This condition can be prevented by regular and focused ANC by midwives who are skilled at therapeutic communication so that the visit of K1-K4 pregnant women can be realized. Pekanbaru has a coverage of K4 pregnant women visits that are still below the target, lower than K4 coverage in several other districts in Riau Province, one of the causes is due to the lack of maximal therapeutic communication for midwives in providing midwifery care. The purpose of this study was to determine how the stages of Therapeutic Communication of Midwives Delima in Antenatal Care services in Pekanbaru City. This study uses a qualitative approach, observation techniques, in-depth interviews, literature and documentation. The data collection technique was purposive, the informants were 4 midwives, 4 pregnant women patients in 4 clinics in the city of Pekanbaru. This research approach uses the phenomenological method with constructivism paradigm and symbolic interactionism theory. The results showed that the therapeutic communication performed by the midwife was not in accordance with the recommended therapeutic communication phases so that the benefits of the care were not maximized.